Voltammetric detection of arsenic (III) using gold nanoparticles modified carbon screen printed electrodes: Application for facile and rapid analysis in commercial apple juice. (1st August 2021) - Sullivan, Connor; Lu, Dingnan; Senecal, Andre; Kurup, Pradeep
Highlights: Gold nanoparticles modified screen printed electrodes for arsenic(III) detection. Arsenic(III) was detected at 0–150 μg L −1 in 5 different apple juice samples. An accurate peak measurement algorithm overcame interference from ascorbic acid. Comparison of voltammetry to atomic absorption spectroscopy showed strong agreement. Abstract: This paper describes a voltammetric method and data analysis program developed for the detection of arsenic(III) in commercial apple juice. Arsenic(III) was detected using square wave stripping voltammetry with gold nanoparticle modified screen printed electrodes. The only sample pretreatment performed was the addition of a 100 mM phosphate buffer with a pH of 7. To compensate for interference from high ascorbic acid concentrations, a data analysis program was developed in MATLAB to fit a non-linear baseline, allowing for accurate peak height measurement. With this data analysis program, the developed methodology had a sensitivity of 0.1007 µA (µg L −1 ) −1 and a limit of detection of 16.73 µg L −1 . A comparison between the voltammetric method and graphite furnace atomic absorption spectroscopy showed no bias in the voltammetric results and a good correlation between the two sets of predicted concentrations, with an R 2 of 0.939.